2021
DOI: 10.48550/arxiv.2111.05530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nearly Optimal Linear Convergence of Stochastic Primal-Dual Methods for Linear Programming

Abstract: There is a recent interest on first-order methods for linear programming (LP). In this paper, we propose a stochastic algorithm using variance reduction and restarts for solving sharp primaldual problems such as LP. We show that the proposed stochastic method exhibits a linear convergence rate for sharp instances with a high probability, which improves the complexity of the existing deterministic and stochastic algorithms. In addition, we propose an efficient coordinate-based stochastic oracle for unconstraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The first two examples, bilinear problem and linear programming, are direct consequences of the following lemmas [4,41]. Lemma 1.…”
Section: A Appendixmentioning
confidence: 99%
See 2 more Smart Citations
“…The first two examples, bilinear problem and linear programming, are direct consequences of the following lemmas [4,41]. Lemma 1.…”
Section: A Appendixmentioning
confidence: 99%
“…Later, [10] presented a simplified and unified analysis for the ergodic rate of PDHG. More recently, many variants of PDHG have been proposed, including adaptive version [51,43,47,24] and stochastic version [8,1,41]. It was also shown that PDHG is equivalent to DRS up to a linear transformation [46,39].…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation